Hume's minimal theism and the supervised Christian church a philosophical and historical analysis of the idea of true religion - Hartl, Péter (Palgrave Macmillan, 2024)
Zusammenfassung: In this book, Péter Hartl offers a novel and comprehensive interpretation of David Hume’s philosophy of religion focusing on various notions of ‘true religion’ in Hume’s overall philosophy and how these ideas relate to various early modern positions on religion, society and philosophy. The account consists of both critical and positive parts of Hume’s overall, nuanced position on theoretical, social and political aspects of religion and the philosophical criticism of religion. Hartl criticises the atheist and completely negative readings of Hume’s philosophy of religion. Instead of presenting Hume’s position as either a radical secularist or closet atheist, Hartl’s interpretation builds on the underdeveloped, positive and constructive parts of Hume’s account of (true) religion. For Hume, on the one hand, true religion is compatible with or even vindicates minimal theism, and it forms part of philosophy exemplifying intellectual virtues.
Keywords: Hume, David -- 1711-1776; Religion--Philosophy.; Religion and sociology.; Psychology and religion.; Religionsphilosophie; Philosophy of Religion.; Sociology of Religion.; Psychology of Religion and Spirituality.; Hochschulschrift